Responses of belowground carbon allocation dynamics to extended shading in mountain grassland. Issue 1 (6th February 2013) - Bahn, Michael; Lattanzi, Fernando A.; Hasibeder, Roland; Wild, Birgit; Koranda, Marianne; Danese, Valentina; Brüggemann, Nicolas; Schmitt, Michael; Siegwolf, Rolf; Richter, Andreas
Summary: Carbon (C) allocation strongly influences plant and soil processes. Short‐term C allocation dynamics in ecosystems and their responses to environmental changes are still poorly understood. Using in situ 13 CO2 pulse labeling, we studied the effects of 1 wk of shading on the transfer of recent photoassimilates between sugars and starch of above‐ and belowground plant organs and to soil microbial communities of a mountain meadow. C allocation to roots and microbial communities was rapid. Shading strongly reduced sucrose and starch concentrations in shoots, but not roots, and affected tracer dynamics in sucrose and starch of shoots, but not roots: recent C was slowly incorporated into root starch irrespective of the shading treatment. Shading reduced leaf respiration more strongly than root respiration. It caused no reduction in the amount of 13 C incorporated into fungi and Gram‐negative bacteria, but increased its residence time. These findings suggest that, under interrupted C supply, belowground C allocation (as reflected by the amount of tracer allocated to root starch, soil microbial communities and belowground respiration) was maintained at the expense of aboveground C status, and that C source strength may affect the turnover of recent plant‐derived C in soil microbial communities.